Cadmium accumulation in rice (Oryza sativa L.) alleviated by basal alkaline fertilizers followed by topdressing of manganese fertilizer. (July 2020) - Deng, Xiao; Chen, Yixuan; Yang, Yang; Lu, Lei; Yuan, Xiaoqing; Zeng, Hongyuan; Zeng, Qingru
Abstract: Rice is a main source of dietary cadmium (Cd), thus, how to reduce the Cd concentration in brown rice has received extensive attention worldwide. In three acidic paddy soils slightly to moderately contaminated with Cd, a series of field experiments were conducted to evaluate the effects of different proportions of nitrogen-phosphorus-potassium (N-P-K) fertilizer (urea, calcium magnesium phosphate, and potassium carbonate, respectively) alone or coupled with a topdressing of manganese (Mn) fertilizer at the tillering stage on reducing Cd bioavailability in soil and uptake in rice. The rational application of N-P-K fertilizer not only provided the basic nutrients to promote the normal growth of rice but also increased soil pH and thereby reduced the Cd bioavailability in soil. The Mg(NO3 )2 -extracted Cd concentrations in the three soils were reduced by 26.46–56.53%, while TCLP-extracted Cd were reduced by 19.87–45.41%, with little influence on soil cation exchange capacity (CEC) and organic matter (OM). The application of Mn fertilizer at the tillering stage increased Mn and Cd sequestration in the iron plaque. The Mn content in iron plaque increased by 15.71–58.67% and a significant positive correlation between Cd and Mn was observed at the three sites. Collectively, this combined method of fertilization significantly reduced Cd accumulation in rice tissues, the Cd concentrations in roots of treated plants decreased by 11.18–37.78%, whereas the concentrations in straw decreased by 13.16–41.03%. Particularly to brown rice, in which accumulation decreased by 25.19–44.70%, 37.35–47.84%, and 38.00–60.88% in three typical paddy fields, but no significant effect was observed for the Cd translocation factors (TF) among rice tissues. Thus, the basal application of combined urea and alkaline inorganic fertilizers followed by topdressing of Mn fertilizer may be a promising and cost-effective tactics for the remediation of Cd-contaminated paddy soils. Graphical abstract: Image 1 Highlights: Basal alkaline fertilizer promoted the growth of rice in acidic Cd-contaminated soil. Basal alkaline fertilizer application decreased the Cd bioavailability in the soil. Topdressing of manganese fertilizer at tillering stage promoted iron plaque formation. Topdressing of manganese fertilizer promoted Cd sequestration in the iron plaque. This combined method was effective in reducing Cd concentrations in rice plants. Abstract : The application of basal combined alkaline inorganic followed by topdressing with manganese fertilizer significantly decreased Cd accumulation in rice tissues.